2006
DOI: 10.1079/asc200632
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive toxicological effects of gossypol on male rabbits: semen characteristics and hormonal levels

Abstract: The objective of this study was to evaluate the effects of two sublethal doses (4 and 20 mg/kg live weight (LW); every other day) of gossypol on semen and hormonal characteristics of male rabbits. The experiment lasted 16 weeks and included two periods: a treatment period (first 8 weeks) where the animals were given the test materials, and a recovery period (second 8 weeks) where drugs were withdrawn. Results showed that LW and respiration rate (RR) decreased ( P , 0·05) among animals that received gossypol, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 37 publications
(41 reference statements)
7
19
0
2
Order By: Relevance
“…This agrees with the present results in which the concentrations of these amino acids were reduced by treatment with gossypol in a dose-dependent manner (Table 1), which was accompanied by severe reduction in sperm concentration (Taha et al, 2006).…”
Section: Amino Acidssupporting
confidence: 93%
See 4 more Smart Citations
“…This agrees with the present results in which the concentrations of these amino acids were reduced by treatment with gossypol in a dose-dependent manner (Table 1), which was accompanied by severe reduction in sperm concentration (Taha et al, 2006).…”
Section: Amino Acidssupporting
confidence: 93%
“…Our studies on the same rabbits showed that this gossypol-induced reduction of seminal amino acids was associated with poor-quality semen, i.e. low concentration, low motility, and increase in dead and abnormal sperm (Taha et al, 2006). This finding coincided with those of Hopwood and Gassner (1962) who reported that increased concentration of seminal total free amino acids was related to the increased quality and fertility of semen, and that poor semen quality was related to amino acids imbalance.…”
Section: Amino Acidssupporting
confidence: 79%
See 3 more Smart Citations